Cyclooxygenase-2 expression correlates with poor prognosis in pancreatic cancer. Issue 4 (7th February 2006) - Juuti, A; Louhimo, J; Nordling, S; Ristimäki, A; Haglund, C
Abstract : Background: Cyclooxygenase-2 (COX-2) overexpression is related to poor outcome in several cancers. COX-2 is upregulated in 42–90% of pancreatic ductal adenocarcinomas and is a potential target for chemotherapy. Earlier studies have not shown the expression of COX-2 to be a prognostic factor in pancreatic cancer. Objective: To evaluate the prognostic value of COX-2 in a series of patients with pancreatic adenocarcinoma. Methods: 128 patients operated on for pancreatic adenocarcinoma at Helsinki University Central Hospital between 1974 and 1998 provided sections from primary tumours which were immunohistochemically stained with a COX-2-antihuman monoclonal antibody. Results: Cytoplasmic COX-2 reactivity (>5%) occurred in 46 specimens (36%), correlating neither with age, sex, stage, size, tumour stage, nodal metastases, nor grade. Lack of COX-2 expression correlated with distant metastases (p = 0.026). In univariate survival analysis, COX-2 expression (p = 0.0114), stage (p = 0.0002), grade (p = 0.0001), and age (p = 0.042) had prognostic significance. One, two, and five year survival rates were 51%, 32%, and 8% in the COX-2 negative groups compared with 34%, 5%, and 5% in the COX-2 positive groups (p = 0.011). Prognostic significance was especially high for patients operated on with curative intent (p = 0.004). In multivariate analysis, COX-2 was an independent prognostic factor (hazard ratio = 1.6 (95% confidence interval, 1.1 to 2.3)). Conclusions: Expression of COX-2 was associated with poor outcome from pancreatic ductal adenocarcinoma and was independent of tumour stage, grade, or age in multivariate analysis.